Envisioning, counting and describing Portuguese colonial populations, 1776-1875: notes from research in progress - Matos, Paulo Teodoro (2017)
By the end of the 18th century, the Portuguese Crown implemented a system for the gathering of demographic data in its overseas domains. In accordance with the model defined, each governor was to send a population count for the area under his jurisdiction annually. At the Arquivo Histórico Ultramarino, in Lisbon, there are over a thousand “population tables” from Brazil to Macao. This documentation significantly broadens horizons for demographic, social and colonial history, despite having been relatively neglected by historians and demographers. These sources allow for the study of demography and statistical processes during the construction of the Portuguese Empire between 1776 and 1875. The context of this research, with an emphasis on the particular characteristics of the sources, the data and their potential, as well as a research agenda shall be discussed further.